Droplet microfluidics in (bio)chemical analysis. Issue 1 (8th October 2014) - Basova, Evgenia Yu; Foret, Frantisek
Abstract : Droplet microfluidics may soon change the paradigm of performing chemical analyses and related instrumentation. Abstract : Droplet microfluidics may soon change the paradigm of performing chemical analyses and related instrumentation. It can improve not only the analysis scale, possibility for sensitivity improvement, and reduced consumption of chemical and biological reagents, but also the speed of performing a variety of unit operations. At present, microfluidic platforms can reproducibly generate monodisperse droplet populations at kHz or higher rates with droplet sizes suitable for high-throughput experiments, single-cell detection or even single molecule analysis. In addition to being used as microreactors with volume in the micro- to femtoliter range, droplet based systems have also been used to directly synthesize particles and encapsulate biological entities for biomedicine and biotechnology applications. This minireview summarizes various droplet microfluidics operations and applications for (bio)chemical assays described in the literature during the past few years.